Boas práticas de manejo de bezerras leiteiras na fase de cria e potenciais efeitos na recria - Silva, Luciana Pontes da [UNESP] (2015)
Human-calves relationship can be improved through gentle tactile interactions. This stimulus can also affect the calves production and animal welfare. The use of European and Zebu crossbreds has gained space for the dairy production in tropical and subtropical regions, however, little it is known about the influence of good handling of practices on the welfare and temperament of crossed cattle. The aim of this study was to understand the longterm effects of the good practices of handling on behavior, performance, physiological stress indicators, and calves health. The first chapter was developed with the purpose of contextualizing the reader about the main subjects of the dissertation. The second chapter, experimental study, was performed with the aim of evaluate the long-term effects of good practice of handling during the preweaning period on dairy calves with different proportions of Zebu breed. Ninety eight newborns calves were used, assigned into three groups of treatments applied during the pre-weaning period: a) good practices of handling plus brushing; b) good practices of handling; and c) Control group. Four temperament evaluations (EV) were performed every two months, using four behavioral indicators: a) time to drive (TD); b) reactivity score (CRS); c) flight speed (FS) and; d) flight distance (FD). Respiratory and heart rates were used as physiological indicators of acute stress during handling. Numbers of occurrences of bovine anaplasmosis and pneumonia per calf during the post-weaning period were obtained. ADG was calculated based on body weight in the time of EV. Treatments had significant effects (P < 0.05) in three temperament traits: TD, FS, and FD, but not in CRS (P = 0.78). In the first three EV the Control group had lower TD means (EV1: 25.40 ± 6.21; EV2: 9.52 ± 3.69 and EV3: 23.90 ± 3.99) than GPB (EV1: 38.63 ± 7.20; EV2: 13.66 ± 3.93 and EV3: 35.45 ± 4.66) and GP groups (EV1: 41.53 ± 7.60; EV2 ...